Turbine Governing System at PT PLN Indonesia Power PLTU Banten 2 Labuan - Esa Mi'rajuddin, Septa; Supriyatna, Deddy; Putra, Ricky Cahyasari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the performance of the Turbine Governing System in a 100 MW steam turbine in maintaining power system frequency stability through the regulation of the steam chest, governor valve, and Emergency Stop Valve (ESV) under load variations of ±10% from the nominal power. The research employs a descriptive quantitative approach based on literature studies, supported by dynamic modeling and system response simulations under a droop configuration of 4–5%. The results show that a 10% load increase causes an initial frequency deviation of 0.18–0.22 Hz from the nominal 50 Hz, with an initial governor valve response time of 0.25–0.35 seconds and a settling time of 4–6 seconds, which remain within the standard operational limits of power systems. A 4% droop configuration produces a faster frequency response but with greater power overshoot (5–6%), while a 5% droop configuration provides better power stability with lower overshoot (3–4%), indicating a trade-off between response speed and system stability. The steam chest dynamic analysis reveals that an increase in the steam pressure time constant can slow frequency recovery by up to 18–22%. Under extreme disturbance conditions, the ESV is capable of closing within 0.15–0.20 seconds, effectively preventing turbine overspeed. These findings highlight that frequency stability is determined not only by the generating capacity of the power plant but also by the quality of dynamic response and the integrated coordination among the steam chest, governor valve, and ESV. This coordination becomes increasingly strategic in supporting the flexibility and reliability of power systems amid the growing penetration of renewable energy.